Synthesis of Novel Polyacrylamide with 4-Arm and Flocculation Behaviour in Treating Wastewater - Li, Cuiqin; Kang, Weiwei; Shi, Weiguang; Shang, Hongzhi; Wang, Jun (Asian Journal of Chemistry, 2015)
A novel non-ionic star polyacrylamide was prepared using ceric ammonium nitrate and pentaerythritol as redox initiation system at 47 °C in aqueous medium. The non-ionic star polyacrylamide has been characterized by FT-IR spectroscopy, 1H NMR spectroscopy, gel permeation chromatography (GPC), thermal analysis (DTG) and intrinsic viscosity measurement. The weight-average molecular weight of the star polyacrylamide with 4-arm was 4.67 × 106 and the star polyacrylamide has better heat-resistant performance than linear polyacrylimde. The star polyacrylamide was applied as flocculation systems. The results indicated that the dual-component system was superior to the single one. In conjunction with an inorganic polymeric aluminum (PA), effective flocculation was achieved by the star polyacrylamide. Meanwhile, the amount of star polyarylamide required was significantly lowered, compared with the single system of star polyacrylamide. Temperature, shear and pH effects were investigated to identify optimum application conditions for the flocculation.